Studies on Prognosis in Anisometropic Amblyopia - TAKAKI, Mariko; HOASHI, Yumiko; KAWAKAMI, Natumi (JAPANESE ORTHOPTIC JOURNAL, 1991)
The present study was undertaken to determine the relation between visual acuity of the patients with anisometropic amblyopia and the following factors: (1) age of initial examination, (2) follow-up period, (3) refraction of the amblyopic eye and (4) degree of anisometropia. We studied eighty six patients seen at the Kumamoto University Hospital from 1979 to 1988. Their age on initial examination was ranged from 3 to 15 years. Patients were devided into A-group, composed of patients with final vision of 0.8 or better and B-group, composed of patients with final vision of lower than 0.8. And according to the initial vision, all patients were also devided into C-group, composed of patients with initial vision of 0.3 or better and D-group, composed of patients with initial vision of lower than 0.3. When A-group was compared with B-group, initial vision was lower in B-group. Degree of anisometropia was lower in C-group than in D-group. However, there was no significant difference in the degree of visual improvement between C-group and D-group. No significant relation was found between visual acuity and age of initial examination, follow-up period, degree of anisometropia or refraction of the amblyopic eye.